Regional Income Fluctuations: Common Trends and Common Cycles - Carlino, Gerald; Sill, Keith (The Review of Economics and Statistics, 2001)
This paper investigates trend and cycle dynamics in per capita income for the major U.S. regions during the 1956–1995 period. Cointegration and serial correlation common features information are used in jointly decomposing the series into trend and cycle components. We find considerable differences in the volatility of regional cycles. Controlling for differences in volatility, we find a great deal of comovement in the cyclical response for all regions but the Far West. Possible sources underlying differences in regional cycles are explored, such as the share of a region's income accounted for by manufacturing, defense spending as a proportion of a region's income, oil price shocks, and the stance of monetary policy. Somewhat surprisingly, we find that the share of manufacturing in a region seems to account for little of the variation in regional cycles relative to national cycles, but manufacturing share differentially affects trend growth for four of the seven regions studied.